Analisis Kelayakan Usahatani Tanaman Pangan di Kabupaten Bondowoso Tahun 2021 - Lediana Miravaleri Waju; Markus Patiung; Erna Haryanti Koestedjo (Jurnal Ilmiah Sosio Agribis, 2022)
Bondowoso Regency has quite large prospects for food crops, but the level of feasibility is still unknown. The orientation of farmers in the Bondowoso area is still a sub-system that can only meet family food needs. The research entitled Analysis of the Feasibility of Food Crop Farming in Bondowoso Regency in 2021. The purpose of this research is to analyze the finances of food crop farming in Bondowoso Regency. To analyze the Feasibility of Food Crop Farming in Bondowoso Regency. The type of research used is a survey method conducted in Bondowoso Regency. The sampling technique was carried out using a practical method, namely using the Kretjie Table and the Slovin Formula. The data population in this study is the total number of farmer households in 23 sub-districts in Bondowoso Regency. This research method uses the method of feasibility analysis of farming. With a population of 270 farmers. The results showed that: (1) The cost of farming food crops is Rp. 19,288,500/year. The receipt is Rp. 25,200,000/year. (2) The amount of income (profit) on food crop farming in Bondowoso district is IDR 5,911,500/year. The amount of R/C in food crop farming in Bondowoso district is 1.3 greater than 1. From the results of the feasibility analysis, it shows that food crop farming in Bondowoso district is feasible or provides benefits from a financial aspect.Keywords: Analysis Financial, Farming Feasibility, Food Crops, Profit